Interaksi Sosial Pengikut Ahmadiyah Berbasis Kearifan Lokal di Kabupaten Konawe Selatan - Dewi Anggraini (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2013)
ABSTRACT This study aims to find social interaction based on local wisdom Ahmadiyah followers in Konawe Selatan. Knowing the Islamic doctrines that they understand influence behavior in the Ahmadiyah religious life in Konawe Selatan. This study uses a qualitative, phenomenological approach, there are two point locations are the concentrations of the two beliefs: Sub Wolasi Ranowila village and district in the Village Konda Lamomea. Informants in this study is defined by purposive sampling consisting of the leaders of the Ahmadiyah, Ahmadiyah Board, Local Government. The method of collecting the data in this study using the method of participant observation, interviews, focus group discussions and literature studies. Results showed Ahmadiyah followers in Konawe Selatan goes well and peacefully. This is evident from the dialogue organized by the Ahmadiyah Jamaat and Hizbut Tahrir held in District Konda, Ahmadiyah consistently run three ministerial decree on the ground without any coercion, and the Ahmadiyah Jamaat are active in religious activities and the activities of mutual cooperation, hometown celebration held by the village government used as a form of wisdom from local communities. Islamic doctrines that affect the behavior of followers of Ahmadiyah religious Konawe Selatan. These doctrines were found: a). Organizational vision, b). Thought reference sources, c). Products interpretation, and d) Method. The creation of peace and the Ahmadiyya community in South Konawe can not be separated from aspects: a). Graphic socio religious tolerance images local regional, b). Houses of worship symbols harmony and tolerance awareness, c). Ahmadiyah communication networks, d). Propagation methods and strategic goals. Key words: social interaction, ahmadiyah based, local wisdom